Factors Determining Colorectal Cancer: The Role of the Intestinal Microbiota - Nistal, Esther; Fernández-Fernández, Nereida; Vivas, Santiago; Olcoz, José Luis (Frontiers in Oncology, 2015)
The gastrointestinal tract, in particular the colon, holds a complex community of microorganisms, which are essential for maintaining homeostasis. However, in recent years, many studies have implicated microbiota in the development of colorectal cancer (CRC), with this disease considered a major cause of death in the western world. The mechanisms underlying bacterial contribution in its development are complex and are not yet fully understood. However, there is increasing evidence showing a connection between intestinal microbiota and CRC. Intestinal microorganisms cause the onset and progression of CRC using different mechanisms, such as the induction of a chronic inflammation state, the biosynthesis of genotoxins that interfere with cell cycle regulation, the production of toxic metabolites or heterocyclic amine activation of pro-diet carcinogenic compounds. Despite these advances additional studies in humans and animal models will further decipher the relationship between microbiota and CRC, and aid in developing alternate therapies based on microbiota manipulation.